Орчны дээжинд микроэлемент хортой хүнд метал, цацраг идэвхт изотоп тодорхойлох - S, Gerbish; G, Ganbold; G, Ganchimeg; J, Bayarmaa; B, Dalkhsuren (Scientific transaction of the National University of Mongolia. Physics, 2022)
The present report outlines the activities in Environmental studies at Nuclear Research Center, National University of Mongolia, Ulaanbaatar. The Nuclear and Related Analytical Techniques, which developed in this center, played on very important role in Environmental studies due to several advantageous features as multielemental, accuracy and low detection limits of these methods. The most appreciated advantageof Gamma Spectrometric, with HP Ge detector and Total Reflection X-Ray Fluorescence Techniques are briefly reviewed and • the results on determination toxic heavy metals, trace, natural and man-made radioactive elements in aerosols, soil, water, food and hair samples are discussed in detail. Also, in this report give some results of natural radioactive measurements of soil, building materials and indoor's radon data in Erdenet and Ulaanbaatar cities. In some soil samples of Western Mongolia observed man-made radioisotope Cs-137 14.7-64.8 Bk/kg. It means the Western Mongolia exposed ground and air nuclear explosions at Semipalatinsk (Russia) and Lobnor (China).